2011
DOI: 10.1136/archdischild-2011-300604
|View full text |Cite
|
Sign up to set email alerts
|

Why do children hospitalised with pneumonia not receive antibiotics in primary care?

Abstract: Young children with community-acquired pneumonia may not receive an antibiotic before hospital admission because the illness evolves rapidly or the prescribed medicine is not given by parents. However, missed opportunities for appropriate antibiotic prescribing by health professionals in primary care appear to be common.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 27 publications
(24 reference statements)
0
25
1
Order By: Relevance
“…In a previous New Zealand study, Grant et al observed that 61% of children aged less than 5 years, who were seen in primary care and subsequently hospitalised with community‐acquired pneumonia, received no antibiotics prior to admission . Although this was not associated with increased disease severity, these children were more likely to be bacteraemic.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous New Zealand study, Grant et al observed that 61% of children aged less than 5 years, who were seen in primary care and subsequently hospitalised with community‐acquired pneumonia, received no antibiotics prior to admission . Although this was not associated with increased disease severity, these children were more likely to be bacteraemic.…”
Section: Discussionmentioning
confidence: 99%
“…There is particular concern regarding overuse of antibiotics for children with self-limiting illness [ 7 , 8 ]. At the same time, severe infections are sometimes missed by clinicians and prescriptions not issued [ 9 , 10 ]. Similarly, non-specific abdominal pain in childhood is often under-investigated and over-medicated in primary care [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, delays in care-seeking often occur and can be related to cost, non-recognition of the severity of illness, differences in the perception of the cause of disease, or geographic barriers [8-11]. Additionally, poor healthcare infrastructure and/or lack of appropriate care and medicine contribute to delays [12].…”
Section: Introductionmentioning
confidence: 99%
“…When needed, antibiotic therapy has dramatic effects on child survival; case-fatality rates for treated ALRI are under 1% while untreated ALRI case-fatality rates may reach over 10% [16]. However, there are a number of barriers to receiving appropriate antibiotics at the clinic level, including stock-outs, understaffing, prescribing patterns of health workers, and diagnostic overlaps with other infections [11,12,17,18]. …”
Section: Introductionmentioning
confidence: 99%